Factors related to the advantageous effects of wearing a wetsuit during swimming at different submaximal velocity in triathletes - Tomikawa, A.; Shimoyama, Y.; Nomura, T. (Journal of Science and Medicine in Sport, 2008)
This study was designed to compare the effects of wetsuit (WS) to swimsuit (SS) at identical relative velocities in a swimming flume. Thirteen triathletes performed a continuous progressive swimming test and submaximal steady state swimming tests with a WS and with a SS. Maximal oxygen uptake and the associated velocity at which the was achieved were determined during the continuous progressive tests. Two 5 min swims (at 60% (V60%) and 80% (V80%)) were then conducted to measure, blood lactate concentration (LA), rating of perceived exertion (RPE), the energy cost of swimming (Cs), stroke rate (SR) and stroke length (SL). No difference was found in , but with a WS was 5.4% higher than with a SS. with a WS was lower than with a SS alone at V60%, but not at V80%. Cs with a WS was lower by 14.4% at V60% and 7.5% at V80% than with a SS. No differences were found in LA and RPE between suit conditions during both submaximal swims. Wearing a WS did not affect SL, but SR tended to be higher in a WS for both submaximal velocities. These results suggest that the benefits of wearing a WS are not only improvement in swimming performance and propulsion efficiency, but reduction in gross energy consumption in the swimming portion of triathlon races. Furthermore, when wearing a WS, incremental changes in SR rather than SL are associated with improved swimming performance.